Querns and mills during Roman times at the northern frontier of the Roman Empire (Belgium, northern France, southern Netherlands, western Germany): Unravelling geological and geographical provenances, a multidisciplinary research project. (2016) - , Sibrecht Reniere; , Roland Dreesen; , Gilles Fronteau; , Tatjana Gluhak; , Eric Goemaere; , Else Hartoch; , Paul Picavet; Clercq, Wim De
No abstract available